The Dangers of Cigarette Smoke and the Role of Guided Inquiry for Prevention and Other Prevention - Mochammad Izzur Rizky Aulia; Munasir Munasir; Mohammad Budiyanto; Rizqi Afnan (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: The objectives are to discover the health impact of cigarette smoke, the factors make adolescents’ smoking behavior, and how guided inquiry and other rules for preventing smoking behavior. Method: This research uses a literature review research method or literature study, collecting several sources that can later be used as a reference. This research is obtained from the seventy-five journals reviewed. Results: Based on the literature review, so many destructive impacts of cigarette smoke on health. Mostly factor in smoking behavior is an advertisement of cigarettes. Preventive ways to stop adolescents smoking behavior are also available. Nevertheless, the most effective ways are school-based learning. Primarily health education with guided inquiry learning based. Novelty: Previous research by another researcher needs to explain the factors of adolescent smoking behavior sufficiently; the previous research also needs to mention the prevention of that behavior. This research shows the health impact of smoking and prevention in social life, and this research shows the role of guided inquiry for prevention.